2016
DOI: 10.1080/15376516.2016.1175530
|View full text |Cite
|
Sign up to set email alerts
|

Does photocatalytic activity of TiO2 nanoparticles correspond to photo-cytotoxicity? Cellular uptake of TiO2 nanoparticles is important in their photo-cytotoxicity

Abstract: Titanium dioxide (TiO2) nanoparticles are important industrial nano-objects with wide applications, including as photocatalysts and sunscreen components. Recently, the phototoxicity of TiO2 nanoparticles has been a concern. However, phototoxicity caused by photocatalytic activity may differ between anatase and rutile nanoparticles. In the present study, we compared the phototoxicity of anatase and rutile nanoparticles. Human keratinocyte HaCaT cells were treated with stable TiO2 nanoparticle suspensions. Witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…When several nano‐TiO 2 concentrations were tested, a dose‐dependent effect was observed. On the contrary, five studies reported no effect of nano‐TiO 2 (0.1–25 μg/cm 2 or 1–100 μg/mL) on HaCaT cell viability after 2–24 h of exposure, but one of them showed a dose‐dependent increase in apoptosis . Data on nano‐TiO 2 cytotoxicity assessed in human skin cells are presented in Table .…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…When several nano‐TiO 2 concentrations were tested, a dose‐dependent effect was observed. On the contrary, five studies reported no effect of nano‐TiO 2 (0.1–25 μg/cm 2 or 1–100 μg/mL) on HaCaT cell viability after 2–24 h of exposure, but one of them showed a dose‐dependent increase in apoptosis . Data on nano‐TiO 2 cytotoxicity assessed in human skin cells are presented in Table .…”
Section: Toxicitymentioning
confidence: 99%
“…ROS induction in HaCaT cells was shown to be enhanced by UVA and UVB irradiation, but not by UVC irradiation, thus demonstrating phototoxicity of nano‐TiO 2 to human skin keratinocytes. Interestingly, after UVA irradiation, either less or no phototoxicity was observed in HaCaT cells with the rutile form of nano‐TiO 2 in comparison with the anatase form . Of note, no phototoxicity was observed with the anatase form of nano‐TiO 2 in the EpiDerm ™ 3D skin model In contrast to the HaCaT cell line that consists of human immortalized keratinocytes, the EpiDerm™ 3D model is a reconstructed human epidermis with normal human‐derived epidermal keratinocytes that is expected to provide a more integrated response.…”
Section: Toxicitymentioning
confidence: 99%
“…After duplicates removal, 31 studies had their titles and abstracts screened, and 24 studies were excluded because they did not meet the eligibility criteria. Then, the full-text screening did not exclude any studies, resulting in 7 included articles (Park et al, 2011;Choi et al, 2014;Kato et al, 2014;Horie et al, 2016;Kim et al, 2016;Miyani and Hughes, 2016;Tang et al, 2018) in this systematic review (Figure 3 Prisma Flow diagram).…”
Section: Searchmentioning
confidence: 99%
“…The European Food Safety Authority (EFSA) designated the “E number” E171 to TiO 2 , granting it as a substance that can be used as a food additive [ 2 ]. In addition, recent evidence indicates that the use of nanosized titanium dioxide (TiO 2 NPs) in consumer and industrial products has exponentially increased due to their highly valuable refractive, photocatalytic and pigmenting properties [ 3 , 4 ]. Even though TiO 2 was classified by the International Agency for Research on Cancer (IARC) as a possible human carcinogen on group 2B in 2010, the Nanotechnology Consumer Products Inventory has documented around 100 consumer products containing TiNPs and TiO 2 NPs to date [ 5 ].…”
Section: Introductionmentioning
confidence: 99%